The Musculoskeletal Anatomy of the Komodo Dragon’s Hindlimb (Varanus komodoensis, Varanidae) - Anna Tomańska; Martyna Stawinoga; Tomasz Gębarowski; Maciej Janeczek; Joanna Klećkowska-Nawrot; Karolina Goździewska-Harłajczuk; Maciej Dobrzyński (Animals)
The Komodo dragon (Varanus komodoensis) is the largest extant lizard and is classified as an endangered species. Despite its rarity, anatomical studies on this species remain limited, hindering a comprehensive understanding of its biology and evolutionary traits. This research presents a detailed anatomical and histological examination of the pelvic limb of a female Komodo dragon, providing valuable insights into the musculoskeletal system of this species. A series of measurements and observations were made on the bones of the pelvic limb, including the femur, tibia, fibula, and pes, all of which are essential for supporting the animal’s large body size and facilitating its predatory behavior. This study also highlights the diverse muscle architecture, where large muscle masses are associated with the femoral retractors and ankle plantarflexors. Histological analysis of the muscle fibers revealed significant variability in fiber diameters, supporting the functional adaptation of the Komodo dragon’s limbs for high-speed ambush predation. This research provides important morphological data that could inform clinical practices, including orthopedic procedures and physiotherapy for Komodo dragons in zoological settings. Additionally, these findings shed light on the evolutionary patterns inherited from the species’ ancestors, which contributed to the development of its distinctive biological adaptations.